The high-throughput screening system for inhibitor Mycobacterium tuberculosis compounds based on ATP hydrolysis activity of recombinant protein ClpC1 - Duc, Nguyen Minh; Lee, Hanki; Won Suh, Joo; Bich Thuy, Vo Thi; Ngoc Minh, Nghiem; Phan Lan Hong, Nguyen (Vietnam Journal of Biotechnology, 2020)
The global Tuberculosis (TB) rate continues to increase by 1% per year with the widespread of drug-resistant TB. Therefore, the development and research to find new anti-TB drugs are becoming an extremely urgent mission. To be able to screen lead anti-tuberculosis drugs, currently, researchers have to carry out directly on the cells of Mycobacterium tuberculosis and to be performed in bio-security facilities level 3 or 4, to prevent infection from pathogens. However, our results demonstrated that the screening of anti-TB drug candidates can be implemented in bio-security facilities level 1 laboratory with the Escherichia coli cell extraction and recombinant ClpC1 protein - an integral part of the Mycobacterium tuberculosis genome. We focused on the ATP hydrolysis activity of ClpC1 to create a specific research direction for the high-throughput anti-tuberculosis drug screening system. ClpC1 protein was overexpressed and purified with functionally characterized (93.5 kDa). The steady-state growth of recombinant ClpC1 protein in Luria-Bertani (LB) broth High Salt medium was maintained and stabilized after extraction. The determined ATPase activity of ClpC1 was performed by measuring the released phosphate from the reaction. Ecumicin was chosen to be a control compound with expected ATP hydrolysis activities (Hill coefficient = 1,19 ± 0,217; Kd value = 0,52 ± 0,275). We tested this high throughput screening system with ten anti-TB drugs to evaluate the effectiveness of our screening system. Based on these results, we built a complete high-throughput screening system anti-tuberculosis drug safety and quickly.